Long-term effects of forest growth dynamics and climate change on groundwater recharge and evapotranspiration in a steep catchment of western Japan - Rendilicha Halake Guyo; Kunyang Wang; Shin-ichi Onodera; Mitsuyo Saito; Toshitsugu Moroizumi (Ecological Indicators, 2025)
Growing water demand for human and environmental needs has led to increased reliance on groundwater resources. However, groundwater is a finite resource, and its sustainability is closely linked to recharge processes, which are influenced by forest growth dynamics as well as climate change. Evapotranspiration, largely driven by vegetation cover and climatic conditions, represents a major component of terrestrial water loss that can reduce groundwater recharge. In this study, forest growth trends, reflecting the complete developmental stages from juvenile to post-maturity of a representative species, were reconstructed using remote sensing data, forest inventories, and field studies, and incorporated into the SWAT model to evaluate their impacts on groundwater recharge and evapotranspiration as indicators of forest hydrological function and ecosystem health. The model’s vegetation growth simulation was enhanced and uncertainty reduced by dynamically updating it with MODIS-derived leaf area index (LAI) at 5-year intervals. Groundwater recharge estimates were further improved through multi-variable calibration using Penman–Monteith–Leuning evapotranspiration (V2) and streamflow data to ensure water budget closure. Results showed that evergreen conifer growth from planting to maturity significantly reduced groundwater recharge (–4.7 mm/year) and increased evapotranspiration (+7.6 mm/year). In contrast, natural and mature deciduous broadleaf forests showed more stable recharge and evapotranspiration trends. Rising temperatures were identified as a key climatic driver of reduced recharge and increased evapotranspiration, reflecting broader global warming impacts. This study demonstrates that forest growth dynamics, especially during the critical transition from planting to maturity, alongside climate change, play a crucial role in shaping the catchment’s water balance and offer valuable insights for sustainable groundwater management, particularly in transitional forest ecosystems.